P141 COMPARISON BETWEEN TECHNIQUES OF EVALUATION MICROVASCULAR MORPHOLOGY: THE GOLD-STANDARD LOCALLY INVASIVE MICROMYOGRAPHY VS. THREE NON-INVASIVE TECHNIQUES. PRELIMINARY DATA - C. De Ciuceis; S. Caletti; M.A. Coschignano; C. Rossini; S. Duse; F. Docchio; S. Pasinetti; F. Zambonardi; F. Semeraro; G. Sansoni; C. Agabiti Rosei; P. Pileri; et al. (Artery Research, 2017)
Objective: The gold standard technique of evaluation microvascular morphology in human is generally considered the measure of media to lumen ratio (M/L) of subcutaneous small vessels obtained by local biopsies and evaluated by wire or pressure micromyography. However, non-invasive techniques for the evaluation of retinal arterioles were recently proposed, in particular two approaches seem to provide interesting information: Scanning Laser Doppler Flowmetry (SLDF) and adaptive optics (AO); both of them provide an estimation of the wall to lumen ratio (WLR) of retinal arterioles. A non-invasive measurement of basal and total capillary density may be obtained by videomicroscopy/capillaroscopy. No direct comparison of the non-invasive techniques in the same population was previously performed, in particular AO was never validated against micromyography. Methods: In the present study, we enrolled 12 normotensive subjects and 8 hypertensive patients undergoing an election surgical intervention; (11/20 were severely obese). All patients underwent a biopsy of subcutaneous fat during surgery. Subcutaneous small resistance artery structure was assessed by wire myography and the M/L was calculated. WLR of retinal arterioles was obtained by SLDF and AO (SLDF, Heidelberg Engineering, Heidelberg, Germany and RTX-1, Imagine Eyes, Orsay, France). Functional (basal) and structural (total) microvascular density were evaluated by capillaroscopy before and after venous congestion. Results: The results are summarized in the Table (slope of the relation: p < 0.01 RTX-1 vs. SLDF).